The kokinshū : selected poems - Duthie, Torquil (Translations from the Asian classics., 2023)
"The Kokinshu is a thematically divided tenth-century collection of 1,111 Japanese waka poems that was imperially commissioned. For over a thousand years, it was the major source for the associations, motifs, and styles of the Japanese vernacular poetic tradition. Poetic and prose texts as diverse as The Tale of Genji, The Pillow Book, and Basho's haikai poetry all draw from the Kokinshu, making this a foundational work for the study of classical Japanese literature. Duthie's new translation has the specific merit of using the formulaic poetic language that characterizes waka poems in a consistent way. In this volume, he presents a selection of the poems, preserving their narrative sequence, and an introduction geared to classroom use"--